Incremental Value of Three-Dimensional Echocardiography over Two-Dimensional Echocardiography in the Assessment of Atrial Septal Defects (Cardiovascular Journal, 2015)
Abstract not available DOI: http://dx.doi.org/10.3329/cardio.v7i2.22243 Cardiovasc. j. 2015; 7(2): 67-71